Kreativitas Guru Ekonomi Dalam Menerapkan Model Pembelajaran di Era Digital/Revolusi 4.0 Di SMA Negeri 2 Palangka Raya - Riska Riska; Rinto Alexandro; Tonich Uda; Sri Rohaetin; Nonsihai Nonsihai; Susi Sukarningsi; Hendrowanto Nibel; Susan Daniel (FKIP, Universitas Palangka Raya, 2023)
In the era of the industrial revolution 4.0, new technologies emerged that resulted in extraordinary changes in all fields, including education. Technology continues to change, becoming faster or cheaper, this requires the world of education to construct creativity, critical thinking, mastery of technology, and digital literacy skills. In fact, currently we need the best teachers who understand class dynamics and utilize technology to educate students. Technology will make teachers more confident and easier in teaching their students so that they are able to turn classrooms into creative, innovative and fun learning spaces. This study aims to determine the creativity of economics teachers in implementing learning models in the digital era/revolution 4.0 at SMA Negeri 2 Palangka Raya. The research method used seen from the type of research is qualitative research emphasizing meaning, reasoning, definition of a particular situation related to the problem of creativity of economics subject teachers in applying learning models, data collection process using observation, interviews, documentation using descriptive analysis techniques, so see the truth. Teacher creativity in applying learning models using Blended learning and Cloud learning models and learning planning using Learning Implementation Plans (RPP) that are oriented towards learning that can form creative and innovative generations. The implementation of learning in schools is also supported by learning infrastructure that is sufficient to help become the basis for learning for the success of understanding in students, so that teachers can become facilitators who will guide students in the learning process. The use of technology by economics teachers at SMA Negeri 2 Palangka Raya as a tool in implementing learning is to use google classroom, google meet, whatsapp, zoom, PPT, self-made videos or from the internet according to learning objectives. In planning indicators, teachers require routine annual teaching and learning activities/Technical Guidance (Bimtek) which are held through school programs or the city government. In the implementation indicators, the importance of mastery of infrastructure goods in the modern era, in this growing era, we are required to always be active so that teachers are not left behind and learning reaches effective and efficient goals. Evaluation indicators for teachers are expected to always be active in introducing students' characters, increasing references to modern learning modules so that students can plan optimally and be more interesting in the future.